The molecular design of photo-curable and high-strength benzoxazine for 3D printing - Lu, Yong (2022)
Low viscosity photo-curable benzoxazines (BZs) are designed and synthesized for use in stereolithography 3D printing. An initial investigation shows that the thermally polymerized polybenzoxazines (PBZs) have remarkably high T-g (264 degrees C) and flexural modulus (4.91 GPa) values. Subsequently, the formulated photoprintable resins are employed for use in high-resolution projection micro-stereolithography (P mu SL) printing. Complex PBZ 3D structures can be achieved from the as-printed objects after they are thermally treated. These findings advance the design of BZ monomers for photopolymerization-based 3D printing and offer a method for the efficient fabrication of high-performance thermosets for various demanding engineering applications.